Xác định hàm lượng Piperin trong hồ tiêu ở tỉnh Kon Tum bằng phương pháp quang phổ hấp thụ phân tử UV-VIS. - Le, Kim Phung Nguyen (2025)
Piperine is the most major alkaloid in pepper. It plays an important role in determining the value of pepper. Piperine content was extracted by the Soxhlet extraction method for 3.5 hours and measured at 343 nm by an UV-VIS molecular absorption spectrophotometer. After surveying, the repeatability of green and black pepper samples was from 1.76 to 2.07% and from 3.79 to 4.85%, respectively, and the laboratory's reproducibility was from 2.0 to 2.24% for green pepper and from 3.81 to 5.48% for black pepper, the recovery was from 87.2 to 91.4% for green pepper and from 84.4 to 89.2% for black pepper. Results showed that the Piperine content in green pepper samples was from 5.23 to 10.2% and 0.77 to 5.31% for black peper.